PENGARUH PENGGUNAAN BAHAN BAKAR BIOETANOL TERHADAP EMISI GAS BUANG KENDARAAN BERMOTOR MESIN BENSIN (OTTO) PADA SIKLUS URBAN (UC) DAN EKSTRA URBAN (EUC) - Puji Lestari (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
Bio-ethanol is one of fuel alternatives which has several advantages when compared to gasoline. Bio-ethanol has recently been used for blended fuel because of the impact to the emission and engine performance (fuel consumption). It has low emission due to oxygenated fuel as well as high octane number, heat value, and volatility. In this study Bio-ethanol from sugar cane was used in the experiments. For this study, cars with Carburetor and Fuel Injection systems were tested using a chassis dynamometer and run according to the Euro 2 standard which has two cycles, urban cycles and extra urban cycles. Each car was tested three times using different type of blended fuels which were BE 0 (0% of bio-ethanol), BE 5 (5% bio-ethanol) and BE 10 (10% bio-ethanol). The results of the experiments show that emission concentration at Urban Cycle higher than Extra Urban Cycle. Blended fuel with bio-ethanol could reduce emission of Particulate, CO and CO2. Using blended fuel (bio-ethanol-gasoline) also could reduce fuel consumption for both types of cars. The emission reduction can be observed clearly for vehicle with carburetor technology.